River of change peace dividends along the Mekong / produced by the Information Office, Asian Development Bank. - Asian Development Bank. Information Office (Manila Asian Development Bank, 1995)
For centuries, the Mekong River has enticed emissaries and exploreres, travelers and traders, into the heart of Southeast Asia. Today, in an era of peace, subregional economic cooperation is bringing hope and change to the people of the Mekong.
Keywords: Economic development projects -- Mekong River Valley; Mekong River Valley -- Economic conditions; Mekong River Valley -- Economic policy; Mekong River Valley -- Economic integration